Synergetic effects of a low caffeine dose and pre-exercise music on psychophysical performance in female taekwondo athletes - Slaheddine Delleli; Ibrahim Ouergui; Hamdi Messaoudi; Craig Alan Bridge; Luca Paolo Ardigò; Hamdi Chtourou (Universidad de León, 2024)
The ergogenecity of caffeine (CAF) and pre-exercise music have been studied extensively in male and mixed-gender groups, but there is limited information on their synergistic effects in females. This study assessed the effects of combining a low dose of CAF with warm-up music on taekwondo specific performance, perceived exertion (RPE), and psychological aspects in female athletes. In a double-blinded, randomized, placebo-controlled crossover study, 16 female taekwondo athletes (M ± SD; age: 17.69 ± 0.60 years) performed the taekwondo-specific agility test (TSAT), 10 s frequency speed of kick test (FSKT-10s) and its multiple version (FSKT-mult) under the following conditions: 1) no supplement with music (NS+M); 2) no supplement without music (control); 3) CAF without music (CAF+NM), 4) placebo without music (PL+NM), 5) CAF with music (CAF+M), 6) PL with music (PL+M). After each test, athletes rated their RPE, feeling scale (FS), felt arousal scale (FAS) and physical enjoyment (PACES). CAF+M induced better physical performance than other conditions on the FSKT-10s, FSKT-mult, and more desirable psychophysiological responses including RPE post_TSAT, RPE post_FSKT-10s, PACES post_FSKT-10s, FS, FAS post_warm-up, FAS post_FSKT-10s and FAS post_FSKT-mult (all p < 0.05). Except for PL+M, CAF+M also elicited more desirable responses than other conditions for FAS post_TSAT (p < 0.05). Furthermore, CAF+M and CAF+NM conditions enhanced TSAT, PACES post_TSAT, RPE post_FSKT-mult greater than the other conditions (p < 0.05). Preceding warm-up music stimulus with a low dose of CAF may be a more efficient strategy to enhance physical performance and affective valence in female taekwondo athletes compared with using either strategy in isolation.